Relative cost-effectiveness of an extensively hydrolyzed casein formula containing the probiotic Lactobacillus rhamnosus GG in managing infants with cow's milk allergy in Italy - Guest JF; Panca M; Ovcinnikova O; Nocerino R (Dove Medical Press, 2015)
Julian F Guest,1,2 Monica Panca,1 Olga Ovcinnikova,1 Rita Nocerino3 1CATALYST Health Economics Consultants, Northwood, Middlesex, UK; 2Faculty of Life Sciences and Medicine, King's College, London, UK; 3Department of Translational Medical Science, Pediatric Section, University of Naples 'Federico II', Naples, Italy Objective: To estimate the cost-effectiveness of using an extensively hydrolyzed casein formula (eHCF) containing the probiotic Lactobacillus rhamnosus GG, (eHCF + LGG; Nutramigen LGG) as first-line management for cow's milk allergy (CMA) compared with eHCF alone, soy-based formulae (SBF), hydrolyzed rice formulae (HRF), and amino acid formulae (AAF) in Italy, from the perspective of the Italian National Health Service (INHS) and parents. Methods: Decision modeling was used to estimate the probability of infants developing tolerance to cow's milk by 18 months, based on an observational study dataset. The model also estimated the cost (at 2012/2013 prices) of health care resource use funded by the INHS and formulae paid for by parents over 18 months after starting a formula, as well as the relative cost-effectiveness of each of the formulae. Results: The probability of developing tolerance to cow's milk by 18 months was higher among infants with either IgE-mediated or non-IgE-mediated allergy who were fed eHCF + LGG compared to those fed one of the other formulae. The total health care cost of initially feeding infants with eHCF + LGG was less than that of feeding infants with one of the other formulae. Hence, eHCF + LGG affords the greatest value for money to both the INHS and parents of infants with either IgE-mediated or non-IgE-mediated CMA. Conclusion: Using eHCF + LGG instead of eHCF, SBF, HRF, or an AAF for first-line management of newly diagnosed infants with CMA in Italy affords a cost-effective use of publicly funded resources, and is cost-effective from the parents' perspective, since it improves outcome for less cost. A randomized controlled study showing faster tolerance development in children receiving a probiotic-containing formula is required before this conclusion can be confirmed. Keywords: amino acid formula, extensively hydrolyzed formula, soy-based formulae, hydrolyzed rice formulae